Exploring variations in sports motivation across menstrual cycle phases: Insights from a longitudinal within-subjects study with active females - Reusch, Laura; Zunner, Beate; Tittlbach, Susanne; Herfet, Melinda (Performance enhancement & health (Oxford), 2025)
Inactivity, as one of the leading risk factors for global mortality, highlights the need for a deeper understanding of how to foster sports motivation. Given the hormonal fluctuations during menstrual cycle phases, it has been suggested that sports motivation may vary as sex hormones impact other areas such as training, emotions, and perception. However, there are inconsistencies in previous studies attributed to varying methodologies in menstrual phase classification and verification. Hence, the main aim of this study was to explore variations in sports motivation across menstrual cycle phases using recommended methods. This longitudinal within-subjects study investigated 17 healthy active females (mean age: 28.1 ± 5.3, body mass index: 22.5 ± 2.5 kg/m2) across three menstrual cycles. Using the mPath App, participants completed daily questionnaires that assessed their sports motivation, menstrual cycle day, and sports program. To determine menses and ovulation during the participant’s menstrual cycle, calendar-based counting and luteinizing hormone testing were employed. Motivation scores were highest during mid-follicular days and periovulatory days, although the overall differences between the menstrual cycle phases were insignificant. Positive correlations were found between periovulatory sports motivation and sport session frequency, and negative between periovulatory sport session intensity and frequency. This study offers new insights for sports motivation and menstrual cycle research, suggesting that there are no significant differences in sports motivation across the hormonal events of the menstrual cycle. Additional factors like coaching, social support, and enjoyment of exercise may also exert influence and therefore warrant further investigation through mixed-method strategies to investigate these psychosocial factors alongside to the menstrual cycle. Future research should replicate these findings using more precise measurements of progesterone and estrogen to enhance methodological accuracy and reliability. [Display omitted]